Pengembangan DeanLEP Application pada Fakultas Sains dan Teknologi UIN Ar-Raniry Banda Aceh - Ima Dwitawati (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2018)
The existence of digital technology should be able to provide a positive and productive impact, rather than the passive and negative one. Technology is enabler that facilitates ubiquitous all human activities both for personal gains and for the public and professional interests. This study aims to develop the DeanLEP application of the Faculty of Science and Technology of UIN Ar-Raniry Banda Aceh. DeanLEP is an acronym for Dean Live Event Page Application that is used to assist the dean in monitoring all daily activities and performance in the faculty. Dean LEP Application contains information about the number of lecturers who teach in the current semester and academic year; recapitulation of active students, on leave students and alumni; lecturers' research, lecturers' ranks, employee permits and leave, study center, lecturers with additional assignments, guest lecturers and guest lectures, women's activities, and cooperatives. In addition to dynamic information updated at any time, Dean LEP Application also provides static information such as information on leaders, lecturers, staff, and contract workers of the faculty.